Quit status and challenges of tobacco users from a tobacco cessation clinic in South India - Sankar, Deepika; Veeraiah, Surendran; Chidambaram, Sundaramoorthy; Sudhakar, Revathy; Swaminathan, Rajaraman (International Journal Of Community Medicine And Public Health, 2022)
In a given time, 55% of smokers and 50% of smokeless tobacco users think of quitting tobacco. However, only 3-5% successfully quit without professional support. This study aims to assess the quit status and challenges of tobacco users enrolled in tobacco cessation clinic at a regional cancer center. Totally, 171 tobacco users above 18 years were enrolled in the TCC between January 2015 and December 2015. All the users were contacted by a psychologist via telephone after 6 months from their first visit for gauging the status of tobacco use, associated challenges for quitting and reasons for not quitting. Nicotine dependence was assessed using the Fagerstrom scale for nicotine dependence for smokers and smokeless tobacco users, separately. Readiness to quit tobacco scale was used to assess the motivational stages of readiness to change. Based on level of nicotine dependence and motivational stage, cessation interventions were provided. On follow-up, 91 (53.2%) were successfully contacted, 72 (42.1%) could not be contacted and 8 (4.6%) had expired. Twenty-six (28.5%) tobacco users had quit and 15 (16.4%) were able to remain abstinent for less than 6 months. Only 5 (12.1%) reported physical challenges and 13 (31.7%) reported psychological challenges while reducing tobacco or quitting. Tobacco cessation provided by trained professionals in a cancer setting has been found to be highly effective in quitting. Close follow-up at regular intervals is mandated to help tobacco users manage cravings and withdrawal symptoms, to assist in achieving quit status.